Comparison of the Effect of Hydrodistillation and Microwave Extraction Methods on the Identified Chemical Composition of Tarragon (Artemisia dracunculus L.) Essential Oil Using Gas Chromatography-mass Spectrometry - M Safaee; SE Hosseini; Sh Shabani (Institue of Medicinal Plants, ACECR, 2016)
Background: Tarragon (Artemisia dracunculus L.) has been utilized as a spice for many years. The essential oil of Tarragon can be used as a natural food preservative since the plant has antioxidant and antimicrobial properties. There has been a variety of methods to extract essential oils. Different methods of extraction might affect extraction rate, percentage and chemical composition amounts of the extracted essential oils. Objective: To find the best method of essential oil extraction, comparing different methods can be performed. In this research two methods of extraction have been compared. Methods: Essential oil of Tarragon was obtained by hydrodistillation and solvent free microwave extraction. Oils were analyzed and the components were identified using gas chromatography-mass spectrometry. Results: The major components of the oil extracted by hydrodistillation were estragol (29.05%) and limonene (11.87%). Estragol (62.40%) and thymol (9.25%) were the major components isolated by microwave free solvent. Conclusion: Considering temperature and time of extraction, different extraction methods make noticeable changes in chemical composition of the oils.